Pengaruh Kehalusan Bahan Dan Lama Ekstraksi Terhadap Mutu Ekstrak Tempuyung (Sonchus arvensis L.) - Feri Manoi (Jurnal Penelitian Pertanian Terapan, 2015)
Utilization of medicinal plants both for health and treatment increased at this time. Number of Traditional Medicine Industry (IOT), Small Industries Traditional Medicine (IKOT) and Industrial Appliances (PIRT) is increasing. Thus the demand for raw materials is increasing, one of which is tempuyung. Good quality raw material in the form of crude drugs and extracts need to be considered as related to the efficacy and quality of products for further processing. The study aims to determine the effect size and the old material extraction to the yield and quality of the extract. Activity consists of two sub-activities (1). How to drying (a) the sun covered with black cloth, (b) the sun combination of tools, and (c) drier. Sub-activities (2) extraction technique which consists of two factors: the fineness of materials (20,40 and 60 mesh) and the second factor is the length of the extraction (2, 4, and 6 hours). The study design using factorial completely randomized design with three replications. Parameter observations consisted of yield bulbs, phytochemical screening, quality characteristics, extract yield, and quality extracts. The results showed levels of water extract Sonchus arvensis L. greater than the levels of alcohol cider. Quality simplicia Sonchus arvensis L. dried using a dryer is not different from the quality of the dried under the sun. Fineness of materials and time of extraction affects the yield of the extract Sonchus arvensis L Keywords: Subtlety material, extraction, quality